A FAMILY WITH HEREDITARY PARAGANGLIOMA SECONDARY TO SDHD MUTATION - SW, Lim; H, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION A third of pheochromocytoma and paraganglioma (PPGL) tumours are part of a hereditary syndrome. Hereditary PPGL shows autosomal dominant inheritance with variable penetrance. Genetic testing is recommended in all patients diagnosed with PPGL regardless of age at presentation and family history. SDHD is the most frequently mutated gene in head and neck PGLs and associated tumours have low malignancy rate. This gene is maternally imprinted with silencing of the maternal allele, thus, the risk of developing paragangliomas is limited to offsprings who inherit the pathogenic variant from their father. Paternally inherited pathogenic variants are highly penetrant by age 50. We describe a family with hereditary paraganglioma due to mutation in the SDHD gene. RESULTS The index patient is a 23 year-old female who was diagnosed to have bilateral adrenal pheochromocytoma with carotid and cardiac paragangliomas. Genetic screening revealed that she has SDHD mutation. Further family history revealed that 2 out of 3 paternal aunts have carotid paragangliomas. Her father, youngest of 5 siblings, paternal uncle and grandfather passed away at age 42, 40, 39 years old, respectively, due to severe headache and possible haemorrhagic stroke. Six other family members underwent genetic screening as well. Five family members were positive for SDHD mutation. These include the index patient’s elder sister, 3 paternal aunts (2 with carotid paragangliomas) and one male cousin. CONCLUSION Genetic testing for family members of patients with hereditary paragangliomas is recommended after thorough genetic counselling. Genetic testing for firstand second-degree relatives is recommended for SDHDrelated paraganglioma. Healthy asymptomatic carriers for the gene mutation should undergo clinical assessment, plasma and/or urine metanephrines and normetanephrines and a combination of whole-body MRI (head and neck, abdominal and pelvic) and PET-CT imaging at initial screening. Thereafter, recommendations for long-term surveillance include annual clinical and biochemical evaluation along with whole body MRI repeated every 2-3 years.